LncRNA polymorphisms in EPF. (1st August 2019) - Lobo‐Alves, S.C.; Augusto, D.G.; Magalhães, W.C.S.; Tarazona‐Santos, E.; Lima‐Costa, M.F.; Barreto, M.L.; Horta, B.L.; de Almeida, R.C.; Petzl‐Erler, M.L.
Summary: Pemphigus foliaceus (PF) is a disease that causes painful blisters in the skin. Due to genetic and environmental reasons, the person's own immune system produces antibodies that attack proteins present in the top layer of the skin (the epidermis). Although PF is rare worldwide, there are some geographic regions where many people develop this disease, known as the endemic form of PF (EPF). In Brazil, EPF is also known as fogo selvagem. This study aimed at finding out if single changes in the DNA (called SNPs – single nucleotide polymorphisms) located in genes called lncRNA genes predispose people to EPF. There are several different variants of SNPs. The frequencies of 2, 080 SNPs were compared between 229 EPF patients and 6, 681 people without pemphigus (the controls). A variant of the SNP called rs7144332 was significantly more frequent among EPF patients than people without EPF, and is therefore associated with increased risk. Results for another five SNPs suggested that they also influence the susceptibility to (risk of) EPF. Further study showed that five of these six SNPs could affect the amount of lncRNAs or proteins produced by nearby genes. Along with other findings, this study shows that genetic variants of lncRNAs might contribute to the development of pemphigus, highlighting their importance in autoimmune and possibly other complex diseases.